2019
DOI: 10.1371/journal.pone.0216611
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of nutritional, biochemical and environmental stimuli on growth performance and fatty acid composition of gilthead sea bream (Sparus aurata)

Abstract: The reliance of the aquafeed industry on marine resources has to be reduced by innovative approaches in fish nutrition. Thus, a three-factorial approach (fish oil reduced diet, phytochemical genistein, and temperature reduction) was chosen to investigate the interaction of effects on growth performance and tissue omega-3 long chain polyunsaturated fatty acid (LC-PUFA) levels in juvenile sea bream ( Sparus aurata , 12.5 ± 2.2 g). Genistein is a phytoestrogen with estrogen-like activity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…The whole‐body dry matter, protein, and lipids were higher in fish reared at 29°C than at 22°C, while ash was not affected by water temperature. In a previous study, it was observed that whole‐body dry matter and lipids of gilthead seabream increased in fish reared from 19 to 23°C (Torno et al, 2019). However, in another study, the whole‐body composition of gilthead seabream juveniles was not affected in fish reared at 18 or 25°C (Couto et al, 2008).…”
Section: Discussionmentioning
confidence: 95%
“…The whole‐body dry matter, protein, and lipids were higher in fish reared at 29°C than at 22°C, while ash was not affected by water temperature. In a previous study, it was observed that whole‐body dry matter and lipids of gilthead seabream increased in fish reared from 19 to 23°C (Torno et al, 2019). However, in another study, the whole‐body composition of gilthead seabream juveniles was not affected in fish reared at 18 or 25°C (Couto et al, 2008).…”
Section: Discussionmentioning
confidence: 95%
“…During the 2010–2020 decade, after the key NRC publication (NRC, 2011), there was an increasing level of definition of requirements for animals of different sizes and in some cases different environmental constraints (e.g., hypoxia, temperature, salinity, etc.). Both age and environmental conditions may markedly affect fish physiology and modulate the expression of key genes, affecting nutrient utilization and nutritional requirements (Fernández‐Palacios et al, 2011; Hamre et al, 2013; Izquierdo & Koven, 2011; Lund et al, 2019; Torno et al, 2019). However, such information is still scattered or absent for some species (e.g., Seriola , Sole) (Sicuro & Luzzana, 2016; Valente et al, 2019).…”
Section: Requirementsmentioning
confidence: 99%
“…Growth is an integrated physiological process in which the ingested energy is converted to biomass. In gilthead seabream, the efficacy of this conversion is regulated by the genetic growth potential of fish and various abiotic factors such as food quality and disponibility, temperature, photoperiod, and salinity [41][42][43]. Like most teleosts, it demonstrates indeterminate growth, with its muscle mass increasing via hyperplasia and hypertrophy throughout its lifespan [18,44,45].…”
Section: Growth Characteristics and Requirementsmentioning
confidence: 99%
“…In addition to the physico-chemical parameters of the aquatic environment, the growth is affected by many other factors, including the genetic component, food availability, and dietary quality [42,49]. Table 1 summarizes the nutritional requirements of gilthead seabream.…”
Section: Growth Characteristics and Requirementsmentioning
confidence: 99%